2010
DOI: 10.1097/brs.0b013e3181cb474f
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Factors Affect Scoliosis Research Society-22 Performance in Healthy Adolescents

Abstract: We report that male gender, dual parent household, white race and increased household income were predictive of higher SRS-22 scores in healthy adolescents without scoliosis. The impact of these factors represents a meaningful clinical difference in SRS-22 performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 17 publications
2
33
2
Order By: Relevance
“…7 The largest series evaluating normative scores in adolescents consisted of 450 patients aged 10 to 21 years. 6 Although there was a mix of race and ethnicities included in the study, there were no normative scores reported for varying ages, nor was there an indication of a power analysis being performed to adequately determine differences between subjects. The study noted differences in SRS-22 scores, with higher scores being reported in Caucasian males from dual, higher income households.…”
mentioning
confidence: 99%
“…7 The largest series evaluating normative scores in adolescents consisted of 450 patients aged 10 to 21 years. 6 Although there was a mix of race and ethnicities included in the study, there were no normative scores reported for varying ages, nor was there an indication of a power analysis being performed to adequately determine differences between subjects. The study noted differences in SRS-22 scores, with higher scores being reported in Caucasian males from dual, higher income households.…”
mentioning
confidence: 99%
“…Race and gender have been associated with significant differences in SRS-22 scores in patients with AIS; however, these differences have not been established in the SK population [17].…”
Section: Discussionmentioning
confidence: 93%
“…Data on these controls, ages 10e21 years, were gathered anonymously from New York public high schools, a major municipal hospital adolescent health clinic and three locally referring pediatrician offices in 2009. Data on this cohort have previously been published; however, only patients with height and weight data from the original study were included in this analysis, resulting in 380 patients in the Control group [17].…”
Section: Methodsmentioning
confidence: 99%
“…18 years), Verma et al [15] reported mean SRS-22 scores of 4.0 in function, 4.3 in pain, 4.2 in image, 3.8 in mental health, and 82 for the subtotal. A comparison between these values and the means obtained in our Un-S group shows that with the exception of the image scale, the preoperative scores of these patients were higher or equal to those reported in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%